2022
DOI: 10.3390/molecules27185780
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Conjugated with Colistin Enhanced the Antimicrobial Activity against Gram-Negative Bacteria

Abstract: Colistin is a potent peptide antibiotic that is effective against Gram-negative bacteria. However, nephrotoxicity limited its clinical use. Silver nanoparticles (AgNPs) have gained attention as a potential antimicrobial agent and nanodrug carrier. The conjugation of antibiotics and AgNPs has been found to increase the activity and decrease drug toxicity. In this study, colistin was conjugated with AgNPs (Col-AgNPs), which was confirmed by Fourier-transform infrared (FT-IR) and energy-dispersive X-ray (EDX) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 56 publications
(95 reference statements)
2
8
0
Order By: Relevance
“…The average particle size of the Ag NPs was estimated using the Debye–Scherrer equation (Equation (2)) [ 42 ]: where D represents the average crystallite size of the Ag NPs, K is the Scherrer constant (with values ranging from 0.9 to 1, accounting for the shape factor), λ is the X-ray wavelength (1.5418 Å), β 1/2 is the width of the XRD peak at half height, and θ is the Bragg angle. Based on the Scherrer equation, the average crystallite size of the Ag NPs was estimated to be approximately 10–20 nm, and the calculated average crystallite size aligned with the grain size range computed by other researchers [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 63%
“…The average particle size of the Ag NPs was estimated using the Debye–Scherrer equation (Equation (2)) [ 42 ]: where D represents the average crystallite size of the Ag NPs, K is the Scherrer constant (with values ranging from 0.9 to 1, accounting for the shape factor), λ is the X-ray wavelength (1.5418 Å), β 1/2 is the width of the XRD peak at half height, and θ is the Bragg angle. Based on the Scherrer equation, the average crystallite size of the Ag NPs was estimated to be approximately 10–20 nm, and the calculated average crystallite size aligned with the grain size range computed by other researchers [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 63%
“…Indeed, this provides a promising therapeutic approach for animals infected with CST-resistant Gram-negative pathogens. A plausible explanation for the observed synergy between the gold complexes and colistin would be in the initial binding of the latter to anionic lipid A molecules of Gram-negative bacteria [ 5 , 6 ], leading to a rapid permeabilization of the outer cell membrane that allows improved penetration of the gold(III) complexes [ 39 , 40 ]. In the absence of colistin, the permeability barrier conferred by the outer membrane of Gram-negative bacteria impairs the transfer of gold complexes to the cytoplasm [ 17 ], so that when CST permeabilizes the bacterial outer membrane, the activity of gold(III) complexes is greatly enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Muenraya et al, Col-AgNPs were found to have higher activity than AgNPs and colistin against Gram-negative bacteria (Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa). According to their results, Col-AgNPs can increase antimicrobial activity and cell biocompatibility more than colistin and AgNPs [51]. In their in vitro studies with silver nanoparticles to investigate antimicrobial activity, Rafq et al reported that diferent concentrations of silver nanoparticles were efective against diferent microorganisms, such as bacteria (E. coli, S. aureus, P. aeruginosa, and K. pneumoniae) and fungi (C. albicans) [52].…”
Section: Antimicrobial Activity Antimicrobial Activities Ofmentioning
confidence: 99%